2009
DOI: 10.1007/s00421-009-1239-7
|View full text |Cite
|
Sign up to set email alerts
|

An EMG frequency-based test for estimating the neuromuscular fatigue threshold during cycle ergometry

Abstract: The purposes of this investigation were twofold: (1) to determine if the model used for estimating the physical working capacity at the fatigue threshold (PWC(FT)) from electromyographic (EMG) amplitude data could be applied to the frequency domain of the signal to derive a new fatigue threshold for cycle ergometry called the mean power frequency fatigue threshold (MPF(FT)), and (2) to compare the power outputs associated with the PWC(FT), MPF(FT), ventilatory threshold (VT), and respiratory compensation point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 37 publications
12
70
1
Order By: Relevance
“…Although neither significant difference (p = 0.060) nor interaction (p = 0.062) has been observed between genders, a phenomenon of different magnitude of EMΔ ( (22)(23)(24)(25)(26)(27) . Bell and Ferguson (28) showed in young women, high correlations of the type I myosin heavy chain in 60 and 75 revolutions per minute in cycle ergometer (r = 0.80 and r = 0.84, respectively), when confronted with the mechanical efficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neither significant difference (p = 0.060) nor interaction (p = 0.062) has been observed between genders, a phenomenon of different magnitude of EMΔ ( (22)(23)(24)(25)(26)(27) . Bell and Ferguson (28) showed in young women, high correlations of the type I myosin heavy chain in 60 and 75 revolutions per minute in cycle ergometer (r = 0.80 and r = 0.84, respectively), when confronted with the mechanical efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Bonne et al (25) showed progressive increase of amplitude of the electromyographic activity, demonstrated by the integrated EMG (iEMG) in maximum exertion tests performed in cycle ergometer. The RMS has been applied to study the increase of the total myoelectrical activity in maximum exertion tests in cycle ergometer and can be applied as an indicator of recruiting of motor units of high excitement threshold (25)(26)(27) . In the present study, the hypothesis of high glycolytic metabolism as well as high RER (table 1) observed in the high work loads was corroborated.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have successfully attempted to use the EMG frequency domain as an index of neuromuscular fatigue during isometric muscle action of the biceps brachii [32][33][34] or the vastus lateralis during cycle ergometry. 24,35 Future studies, however, are needed to validate these new methods and determine their application in rehabilitation settings.…”
Section: Emg Frequencymentioning
confidence: 96%
“…The intersection between the regression line and the y-intercept is identified as the fatigue threshold for that individual, and is theoretically the maximal workload that the individual could continue indefinitely. Recently, Camic and colleagues 24 proposed a method of determining EMG fatigue threshold from a single incremental cycle ergometry test. Briefly, the investigators recorded EMG amplitude from the vastus lateralis at each workload.…”
Section: Utility Of Emg and Mmgmentioning
confidence: 99%
“…Previous studies (deVries et al, 1987(deVries et al, , 1990 have shown that the PWC FT is moderately correlated with the onset of blood lactate, can be determined using only submaximal workbouts, and is sensitive to training adaptations in older populations. The PWC FT test has also been utilized to assess physical fitness (deVries et al, 1987), differentiate fatiguing from non-fatiguing work (deVries et al, 1987), demarcate the moderate and heavy exercise intensity domains (Camic et al, 2010a), examine the physiological mechanisms associated with neuromuscular fatigue (Housh et al, 1991), and evaluate the efficacy of creatine, beta-alanine, and arginine as ergogenic aids (Camic et al, 2010b;Stout et al, 2000Stout et al, , 2008. Furthermore, it has been demonstrated (deVries et al, 1990;Housh et al, 1996) that the PWC FT test is not affected by differences in protocol (i.e.…”
Section: Introductionmentioning
confidence: 99%